Respuesta :

Answer:

The solution to the equation is;

[tex]\begin{gathered} t=-2 \\ r=0 \end{gathered}[/tex]

Explanation:

Given the system of equation:

[tex]\begin{gathered} 6r-3t=6------1 \\ 8t=-6r-16 \\ 8t+6r=-16------2 \end{gathered}[/tex]

Solving by elimination:

Let us subtract equation 1 from equation 2;

[tex]\begin{gathered} 8t+6r-6r-(-3t)=-16-6 \\ 8t+3t=-22 \\ 11t=-22 \\ t=\frac{-22}{11} \\ t=-2 \end{gathered}[/tex]

since t = -2, we can use equation 1 to solve for r;

[tex]\begin{gathered} 6r-3t=6 \\ 6r-3(-2)=6 \\ 6r+6=6 \\ 6r=6-6 \\ 6r=0 \\ r=0 \end{gathered}[/tex]

Therefore, the solution to the equation is;

[tex]\begin{gathered} t=-2 \\ r=0 \end{gathered}[/tex]

RELAXING NOICE
Relax